Germinated Riceberry Rice Enhanced Protocatechuic Acid and Vanillic Acid to Suppress Melanogenesis through Cellular Oxidant-Related Tyrosinase Activity in B16 Cells - Teerapat Rodboon; Seiji Okada; Prasit Suwannalert (MDPI AG, 2020)
The anti-melanogenic bioactivities of phytophenolic compounds have been well recognized. Riceberry rice contains a rich source of phenolic compounds that act as melanin inhibitors through their antioxidant and anti-tyrosinase properties. Germination has been shown to be an effective process to improve targeted phenolic compounds. In this study, germinated riceberry rice extract was tested for antioxidant activity. Total phenolic content was determined while the tyrosinase inhibitory effect was screened by the in vitro mushroom tyrosinase assay. Cytotoxicity of germinated riceberry rice extract was investigated in B16 cells before evaluating its activities on cellular tyrosinase, melanogenesis, melanin excretion, morphological appearance, and cellular oxidants. Germinated riceberry rice extract showed increased potency of antioxidants and was also twice as effective for mushroom tyrosinase inhibition when compared with ungerminated riceberry rice extract. In B16 cells, the extract inhibited cellular tyrosinase, melanogenesis, and cellular oxidants in a dose-dependent manner when compared with untreated cells. Germinated riceberry rice extract also displayed an effect on B16 cells morphology by reducing the number of melanin- containing cells and their dendriticity. Additionally, the germination of riceberry rice dominantly enhanced two phenolic acids, protocatechuic acid and vanillic acid, which have the potential for antioxidant-associated hyperpigmentation control. Thus, the restricted germination of riceberry rice tended to promote protocatechuic acid and vanillic acid, which dominantly displayed antioxidants and tyrosinase-related melanogenic inhibition.